A Review on the Effect of Y-Shaped Twisted Tape on Heat Exchanger Performance - Mohammed, Ansam Adil; Shakir, Ammar Khamees; Channapattana, Shylesha; Srinidhi, Campli; Kamble, Prashant (Al-Nahrain Journal for Engineering Sciences, 2025)
The process of increasing the heat transfer coefficient, resulting in enhancing system efficiency, is known as heat transfer enhancement. Enhancing heat transport is both economically beneficial and a considerable energy conservation problem. To improve heat transfer, many passive components are utilized within tubes, including wire plugs, enhanced surfaces, rough edges, twisted tape inserts, and liquid additives. This study evaluated twisted tape inserts, which are highly effective passive devices. Considering its numerous advantages, such as effortless maintenance, uncomplicated operation, and straightforward production. The twisted tape inserts within the tube generated a vortex and swirling flow. The interior convective heat transfer process is significantly improved. A summary of various twisting tape additives that can boost performance.